Analysis of Legal Protection for Debtors Regarding The Position of Using Standard Contracts in Relation To The Principle of Freedom of Contract on Bank Credit Agreement - Miswanto, Sidik; Ummu Adillah, Siti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research is about